2023
DOI: 10.1039/d3ra04182d
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, in silico studies, and biological evaluation of novel pyrimidine-5-carbonitrile derivatives as potential anti-proliferative agents, VEGFR-2 inhibitors and apoptotic inducers

Abstract: A novel series of pyrimidine-5-carbonitrile derivatives bearing benzylidene and hydrazone moieties with different linkers (spacers) were designed and synthesized as possible inhibitors of the vascular endothelial growth factor receptor-2 (VEGFR-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Our study demonstrated the vulnerability of β cells to IMI-induced reactive oxygen species (ROS), resulting in reduced insulin production and elevated blood glucose levels. However, the administration of lycopene reversed these detrimental effects [32]. Similarly, our study demonstrated that lycopene reduced amylase levels and blood glucose while increasing plasma insulin values [37].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study demonstrated the vulnerability of β cells to IMI-induced reactive oxygen species (ROS), resulting in reduced insulin production and elevated blood glucose levels. However, the administration of lycopene reversed these detrimental effects [32]. Similarly, our study demonstrated that lycopene reduced amylase levels and blood glucose while increasing plasma insulin values [37].…”
Section: Discussionsupporting
confidence: 68%
“…Lycopene is a red carotenoid hydrocarbon found in various red produce, including tomatoes, red carrots, watermelons, grapefruits, and papaya. This hydrocarbon is renowned for its antioxidant and anti-inflammatory properties [32,33]. Our study is the first in the literature to investigate and report on the protective mechanisms of lycopene against IMI-induced oxidative and inflammatory damage in the pancreas using a rat model.…”
Section: Discussionmentioning
confidence: 94%
“…Despite all of these options, treating cancer remains a huge issue for clinicians and researchers due to the complexity of the disease arising from the unrestrained proliferation and division of aberrant cells within the body, which is triggered by abnormal regulation of multiple signaling pathways. Among these include the dysregulation of many kinases and the overexpression of anti-apoptotic proteins, such as Bcl-2 [ 5 , 6 ]. Some of the available cancer medications are now linked to drug resistance and recurrence, demanding the development of innovative therapeutic strategies, such as conjunction medicines, which target several signaling pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%